Internet Self–Efficacy and Task Strategies of EFL Students Teachers within Online Learning Setting - Supriyono, Yusup; Utami Widiati; , Nunung Suryati; Francisca Maria Ivone (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
Online English learning needs individual’ capability to use technology devices and internet wisely and strategy properly. Technology assisted learning is not only about knowing how to operate technology technically, but also to use technology for learning purposes. Due to the problem, this study was aimed to evaluate the internet self-efficacy and task strategies of English as a Foreign Language (EFL) student teachers in an online learning environment. Six participants, representing the third year student teachers from the English education department at a public university in Indonesia, took part in the interview sessions and shared reflective journals. These participants were actively involved in online learning and had been exposed to pedagogical, technological, and English language knowledge for one semester. The data were analysed using thematic analysis, following a qualitative descriptive approach in order to investigate student teachers’ perception on the English online class they had experienced deeply and comprehensively. The findings reveal that internet self-efficacy drives EFL student teachers to use the internet for learning purposes, including sharing and collaboration, building relationship and communication skill, and learning enhancement and enactive learning. Additionally, their task strategies are identified in terms of technology assisted problem solving, digital portfolio and learning resources management, self-control, and meaningful collaboration. Thus, internet self-efficacy and task strategies are the keys to creating effective learning environment. These findings have pedagogical implications, suggesting that learners and teachers should view technology devices as tools to be used strategically to achieve learning objectives, especially in an online English learning context.